2015
DOI: 10.1051/0004-6361/201526295
|View full text |Cite
|
Sign up to set email alerts
|

Modelling circumbinary protoplanetary disks

Abstract: Context. The Kepler mission's discovery of a number of circumbinary planets orbiting close (a p < 1.1 au) to the stellar binary raises questions as to how these planets could have formed given the intense gravitational perturbations the dual stars impart on the disk. The gas component of circumbinary protoplanetary disks is perturbed in a similar manner to the solid, planetesimal dominated counterpart, although the mechanism by which disk eccentricity originates differs. Aims. This is the first work of a serie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 36 publications
3
34
0
Order By: Relevance
“…In simulations concerning circumbinary planets mainly two types of boundary conditions are used: a closed inner boundary (Pierens & Nelson 2013;Lines et al 2015) that does not allow for mass flow onto the central binary, and outflow boundaries (Kley & Haghighipour 2014 that do allow for accretion onto the binary. While Lines et al (2015) do not find a significant difference between these two case, Kley & Haghighipour (2014) see clear impact on the surface density profile and additionally they were able to construct disks with (on average) constant mass flow through the disk which is not possible for closed boundaries. Driven by these discussions in the literature we decided to perform dedicated numerical studies to test the impact of the location of R min , the chosen boundary condition and other numerical aspects in more detail.…”
Section: Arxiv:170408130v1 [Astro-phep] 26 Apr 2017mentioning
confidence: 99%
See 1 more Smart Citation
“…In simulations concerning circumbinary planets mainly two types of boundary conditions are used: a closed inner boundary (Pierens & Nelson 2013;Lines et al 2015) that does not allow for mass flow onto the central binary, and outflow boundaries (Kley & Haghighipour 2014 that do allow for accretion onto the binary. While Lines et al (2015) do not find a significant difference between these two case, Kley & Haghighipour (2014) see clear impact on the surface density profile and additionally they were able to construct disks with (on average) constant mass flow through the disk which is not possible for closed boundaries. Driven by these discussions in the literature we decided to perform dedicated numerical studies to test the impact of the location of R min , the chosen boundary condition and other numerical aspects in more detail.…”
Section: Arxiv:170408130v1 [Astro-phep] 26 Apr 2017mentioning
confidence: 99%
“…For the initial disk setup we follow Lines et al (2015). The initial surface density in all our models is given by…”
Section: Initial Disk Parametersmentioning
confidence: 99%
“…Our work ties together the pure N-body planetesimal dynamics and growth of Lines et al (2014) and the hydrodynamical simulations of circumbinary gas disks of Lines et al (2015). The work is comparable to that of Marzari et al (2013) who investigate the effects of gas disk gravity on the ability for planetesimal to accumulate in the Kepler-16 system.…”
Section: Discussionmentioning
confidence: 93%
“…These fluid parameters are typical of circumbinary disk simulations. Self-gravitating gas disk simulations are ignored, since Lines et al (2015) found that the gas disk only gravitationally interacts with itself for Σ disk ≥ 2.5 × 10 −3 M /au 2 . These hydrodynamical simulations are performed using FARGO-ADSG (Baruteau & Masset 2008;Baruteau 2008) over a polar mesh grid with N r = 395 and N s = 512 where N r and N s are the number of radial and azimuthal cells respectively.…”
Section: Gas Potentialmentioning
confidence: 99%
“…As such it is a surprise that the concept of a mmsn is still used in the consideration of initial conditions for planet forming discs (e.g. Simon et al 2015;Lines et al 2015;Bitsch et al 2015;Hopkins 2016;Coleman et al 2017;Mutter et al 2017) 3 . It is worth stressing that adoption of this could also be explained by FU Orionis type outburst cycles driven by e.g.…”
Section: Initial Conditions For Planet Formationmentioning
confidence: 99%